Signal regulatory protein beta 2 is a novel positive regulator of innate anticancer immunity - Visser, Nienke; Nelemans, Levi Collin; He, Yuan; Lourens, Harm Jan; Corrales, Macarena González; Huls, Gerwin; Wiersma, Valerie R.; Schuringa, Jan Jacob; Bremer, Edwin (Frontiers in Immunology, 2023)
In recent years, the therapeutic (re)activation of innate anticancer immunity has gained prominence, with therapeutic blocking of the interaction of Signal Regulatory Protein (SIRP)-α with its ligand CD47 yielding complete responses in refractory and relapsed B cell lymphoma patients. SIRP-α has as crucial inhibitory role on phagocytes, with e.g., its aberrant activation enabling the escape of cancer cells from immune surveillance. SIRP-α belongs to a family of paired receptors comprised of not only immuneinhibitory, but also putative immune-stimulatory receptors. Here, we report that an as yet uninvestigated SIRP family member, SIRP-beta 2 (SIRP-ß2), is strongly expressed under normal physiological conditions in macrophages and granulocytes at protein level. Endogenous expression of SIRP-ß2 on granulocytes correlated with trogocytosis of cancer cells. Further, ectopic expression of SIRP-ß2 stimulated macrophage adhesion, differentiation and cancer cell phagocytosis as well as potentiated macrophage-mediated activation of T cell Receptor-specific T cell activation. SIRP-ß2 recruited the immune activating adaptor protein DAP12 to positively regulate innate immunity, with the charged lysine 202 of SIRP-ß2 being responsible for interaction with DAP12. Mutation of lysine 202 to leucine lead to a complete loss of the increased adhesion and phagocytosis. In conclusion, SIRP-ß2 is a novel positive regulator of innate anticancer immunity and a potential costimulatory target for innate immunotherapy.